The Neurotoxic Impact Of Lead On The Appearance Of Antisocial Behavior In Batik Dye Workers - Indah Tri Susilowati; Noviana Dewi; Dewi Saroh (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Batik home industry waste not managed with standardized WWTP can lead to environmental pollution. This is caused by the remaining synthetic batik dyes containing heavy metal lead. The remaining dyeing waste is disposed of into the river, a water source in the surrounding environment. Waste containing heavy metals causes a neurotoxic effect on the human body. Furthermore, exposure to heavy metals due to synthetic batik dyes is more at risk for workers who do coloring since they do not use personal protective equipment while working and do not live a clean and healthy lifestyle. One of the behavioral disorders associated with the effects of accumulated lead exposure is an antisocial personality disorder. In this study, blood lead levels were checked for batik dye workers by taking blood samples using a 3 ml purple vacuum tube and placing them in an ice box to be sent to the Yogyakarta Health Laboratory Center (BLK). The blood sample was then wet destroyed, and the Pb levels were read using an AAS tool. Antisocial tendency scale data was measured using STAB (Subtypes of Antisocial Behavior), where the validity test had previously been carried out with the Pearson product-moment of 0.327-0.786 and the reliability test with the Cronbach alpha technique of 0.936. The results of the data analysis showed a correlation between blood lead levels and antisocial disorder tendencies of 0.690, but no correlation was found between blood lead levels and body mass index (BMI)